Integrasi Teknologi dalam Pendidikan Matematika: Wawasan dari Tinjauan Literatur Sistematik: TECHNOLOGY INTEGRATION IN MATHEMATICS EDUCATION: INSIGHTS FROM A SYSTEMATIC LITERATURE REVIEW - Muhammad Fathurrahman; Putri Dini Retno Pratiwi; Marice Awairaro; Nazmi Al-lahmadi; Salima Silayar; Ismail Djakaria (KAMBIK: Journal of Mathematics Education, 2024)
This research aims to conduct a systematic literature review to uncover research trends related to Technology and Mathematics. The research method applied in this study is the Preferred Reporting Items for Systematic Reviews, using 3,812 scholarly articles from the Dimensions database. Article reviews were performed using the VOSviewer application. The results of the studyof reveal that main trends in the "Technology" and "Mathematics" themes over the past five years have focused on the development and integration of technology in the context of mathematics learning. Furthermore, the dominant research issues and themes in this study revolve around the development of learning processes applied by teachers utilizing technology. Relevant research themes for further investigation in relation to "Technology" and "Mathematics" include the integration of technology in mathematics education not only transforming the way we teach and learn but also influencing how curricula are designed, how teachers are trained, and how educational research is approached, all with the aim of creating a more effective, inclusive, and engaging learning experience. The findings of this research contribute to the development of a research roadmap on "Technology" and "Mathematics." The limitation of this study is that the articles used come from the Dimensions database, restricting the scope of the data. Future research is recommended to use articles from databases other than Dimensions, such as the Directory of Open Access Journals (DOAJ), Dimensions, and Google Scholar.